2013
DOI: 10.1109/tbme.2013.2261893
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Superparamagnetic Contrast Agent in Sentinel Lymph Nodes Using Ex Vivo Vibrating Sample Magnetometry

Abstract: As the first step in developing a new clinical technique for the magnetic detection of colorectal sentinel lymph nodes (SLNs), a method is developed to measure the magnetic content in intact, formalin fixated lymph nodes using a vibrating sample magnetometer (VSM). A suspension of superparamagnetic nanoparticles is injected ex vivo around the tumor in the resected colon segments. A selection of three lymph nodes is excised from the region around the tumor and is separately measured in the VSM. The iron content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…VSM allows quantification with 0.5 μg Fe accuracy and is nondestructive, which allows subsequent histopathological analysis of the same samples. 22 …”
Section: Quantification Of Iron Content (Vibrating Sample Magnetometry)mentioning
confidence: 99%
“…VSM allows quantification with 0.5 μg Fe accuracy and is nondestructive, which allows subsequent histopathological analysis of the same samples. 22 …”
Section: Quantification Of Iron Content (Vibrating Sample Magnetometry)mentioning
confidence: 99%
“…Magnetic tracers have several advantages for use in SLNM in CRC. We previously demonstrated that they accumulate in the LNs in CRC after ex vivo administration using nonclinical laboratory equipment [16].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic tracers have several advantages for use in SLNM in CRC. We previously demonstrated that they accumulate in the LNs in CRC after ex vivo administration using nonclinical laboratory equipment . Recently the use of magnetic tracers was also evaluated for SLN biopsy in patients with breast cancer .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 To generate the correct temperatures, accurate knowledge of the spatial MNP distribution is of critical importance. Other MNP-based applications such as drug targeting 5,6 and detection 7,8 also require this knowledge. In this paper, Electron Paramagnetic Resonance (EPR) is employed for recovering the MNP distribution.…”
Section: Introductionmentioning
confidence: 99%